Tannin extracts from immature fruits of Terminalia chebula Fructus Retz. promote cutaneous wound healing in rats - Yu Bo; Zhang Zhen; Wang Shouyu; Zhang Houli; Diao Yunpeng; Li Kun; Huang Shanshan; Yang Hong (BMC, 2011)
Abstract Background Tannins extracted from immature fruits of Terminalia chebula Fructus Retz. are considered as effective components promoting the process of wound healing. The objective of this study is to explore the optimal extraction and purification technology (OEPT) of tannins, while studying the use of this drug in the treatment of a cutaneous wound of rat as well as its antibacterial effects. Methods The content of tannin extracts was measured by the casein method, and antibacterial ability was studied by the micro-dilution method in vitro. In wound healing experiment, animals in group Ⅰ, Ⅱ and Ⅲ were treated with vaseline ointment, tannin extracts (tannin content: 81%) and erythromycin ointment, respectively (5 mg of ointment were applied on each wound). To evaluate the process of wound healing, selected pharmacological and biochemical parameters were applied. Results After optimal extraction and purification, content of tannin extracts was increased to 81%. Tannin extracts showed the inhibition of Staphylococcus aureus and Klebsiella Pneumonia in vitro. After excision of wounds, on days 7 and 10, the percent of wound contraction of group Ⅱ was higher than that of group Ⅰ. After being hurt with wounds, on days 3, 7, and 10, the wound healing quality of group Ⅱ was found to be better than that of group Ⅰ in terms of granulation formation and collagen organization. After wound creation, on day 3, the vascular endothelial growth factor expression of group Ⅱ was higher than that of group Ⅰ. Conclusion The results suggest that tannin extracts from dried immature fruits of Terminalia chebula Fructus Retz. can promote cutaneous wound healing in rats, probably resulting from a powerful anti-bacterial and angiogenic activity of the extracts.